2018
DOI: 10.1001/jamaoncol.2017.4218
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel With and Without Pazopanib for Persistent or Recurrent Ovarian Cancer

Abstract: clinicaltrials.gov Identifier: NCT01468909.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
0
47
0
1
Order By: Relevance
“…Ovarian cancer (OC) is the leading cause of gynecologic cancer deaths and high-grade serous ovarian cancer (HGSOC) is the most common and most lethal histological type [1,2]. The lethality of HGSOC mainly comes from its high risk of recurrence [3,4].…”
mentioning
confidence: 99%
“…Ovarian cancer (OC) is the leading cause of gynecologic cancer deaths and high-grade serous ovarian cancer (HGSOC) is the most common and most lethal histological type [1,2]. The lethality of HGSOC mainly comes from its high risk of recurrence [3,4].…”
mentioning
confidence: 99%
“…Representing a cuttingā€edge breakthrough in drug discovery, allosteric PPI modulators are widely accepted as a possible complement and alternative to orthosteric PPI ligands due to their potential for improved physiochemical and pharmacological properties. Several allosteric PPI modulators have already reached the clinic, such as paclitaxel ( 19 ) and its derivatives targeting Ī±ā€ and Ī²ā€tubulin . Nevertheless, problems such as suboptimal pharmacokinetic properties still exist .…”
Section: Discussionmentioning
confidence: 99%
“…Several allosteric PPI modulators have already reached the clinic, such as paclitaxel (19) and its derivatives targeting Ī±and Ī²-tubulin. 6,8,193,195,[206][207][208][209][210][211][212][213] Nevertheless, problems such as suboptimal pharmacokinetic properties still exist. 6 One of the major obstacles encountered during the development of allosteric PPI modulators is the difficulty in carrying out rational drug design.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have considered the predictive relationship between circulating levels of pro-angiogenic cytokines and response to anti-angiogenics including pazopanib [59][60][61]. The prognostic value of VEGF-A is not clear, and more recently SNPs in VEGF-A and VEGFR1 have shown promise in randomized trials [15,62,63]. We found that only baseline levels of circulating levels of angiopoietin-1 correlated with a reduction in tumor size in keeping with published literature; however, no relationship was observed with PKs [64].…”
Section: Discussionmentioning
confidence: 99%
“…Pazopanib is a pan-VEGF tyrosine kinase inhibitor that has additional inhibitory effects on Ī± and Ī² platelet-derived growth factor (PDGF) receptors, and the proto-oncogene receptor tyrosine kinase (c-KIT) [13]. Two large studies investigated the clinical utility of adding pazopanib to weekly paclitaxel, with conflicting results; with the MITO 11 study reporting a 3-month PFS benefit in patients with platinumresistant disease and the study by Richardson and colleagues reporting no benefit, albeit in a mixed platinum-resistant and platinum-sensitive population [14,15]. Du Bois and colleagues demonstrated an improvement in PFS following the addition of maintenance pazopanib after completion of chemotherapy in platinum-sensitive disease [16].…”
Section: Introductionmentioning
confidence: 99%